Minerals and vitamins in unconventional food plants from Rio Doce valley, Minas Gerais (Brazil) - Cardoso, Leandro De Morais; Almeida, Lionardo Conte De; Silva, Beatriz Souza (Revista de Ciência, Tecnologia e Sociedade, 2025)
Brazil has a diverse flora, with plants with food potential not yet studied. These include unconventional food plants (PANC’s) that can contribute to diversifying and enhanc- ing the quality of human food. This study aimed to investigate the nutritional value of native dandelion (Taraxacum officinale), caruru (Amaranthus viridis) and trapoera- ba (Commelina benghalensis) native from the municipality of Governador Valadares, Minas Gerais. The trapoeraba was a source of magnesium (25.5 mg 100g-1) - good source of calcium (19.28 mg 100g-1), manganese (0.19 mg 100g-1), and zinc (1.29 mg 100g-1) - and excellent source of chromium and iron (35.21 and 51.87 mg 100g- 1). The caruru was a source of calcium (6.37 mg 100g-1), manganese (0.22 mg 100g- 1), and zinc (0.945 mg 100g-1) - good source of potassium (708.75 mg 100g-1) - and excellent source of iron (23.01 mg 100g-1). The dandelion was a source of selenium (0.003 mg 100g-1), copper (0.08 mg 100g-1), molybdenum (0.004 mg 100g-1), and zinc (0.6 mg 100g-1) - and good source of iron (2.35 mg 100g-1) and manganese (0.25 mg 100g-1). Vitamin C and carotenoids (a- and ß- arotene - ß-cryptoxanthin - lycopene) were analyzed by high performance liquid chromatography (HPLC), with diode array detection - vitamin E (a-, ß-, e d- tocopherols and tocotrienols) by HPLC with fluorescence detection - and fourteen minerals were analyzed by atomic absorp- tion spectrometry in inductively coupled plasma. The trapoeraba was the only PANC that presented vitamin C (23.61g 100g-1). The carotenoid content ranged from 7.19 g 100g-1 in the caruru to 31.97g 100g-1 in the trapoeraba. Approximately 98% of the carotenoid content observed in plants corresponded to ß-carotene and the remainder to ß-cryptoxanthin. Dandelion presented the highest total vitamin E content (43.67 μg 100g-1), followed by caruru and trapoeraba (25.74 and 24.08 μg 100g-1, respectively). -Tocopherol and ß-tocotrienol were not identified in any of the PANCs, with a- and -to- copherol being the main components in the caruru and dandelion, each corresponding to approximately 25% of the total content. In trapoeraba, the main components of vi-tamin E were -tocopherol (44.6%) and d-tocopherol (36.8%). The unconventional food plants presented a diversified vitamin profile of vitamins and minerals, highlighting trapoeraba as an important source of these compounds.